Exploring the Landscape of Energy Audits: A Bibliometric Analysis - Oommen, Jishin George; Roy, Noel Simon; Brittoraj, R.D. (International Journal of Energy Economics and Policy, 2024)
The term "sustainability" has emerged as a popular catchphrase for the challenges we face in the twenty-first century, which need a radical rethinking of our economic, social, and environmental practices. Energy audit has evolved as a significant instrument in the search of a sustainable future, and it may be used to leverage other sustainability initiatives. Businesses may actively contribute to a more sustainable future and align operations with global environmental objectives by adopting energy practices. The purpose of this study is to do a bibliometric analysis of scholarly works that discuss energy auditing and its role in promoting sustainability. We may learn more about the major issues, trends, and contributions to green energy audit for sustainable development by reviewing the relevant academic literature.